2015
DOI: 10.5091/plecevo.2015.1013
|View full text |Cite
|
Sign up to set email alerts
|

Specialist plant species harbour higher reproductive performances in recently restored calcareous grasslands than in reference habitats

Abstract: 15Background and aims_Calcareous grasslands are local biodiversity hotspots in temperate 16 regions that suffered intensive fragmentation. Ecological restoration projects took place all 17 over Europe. Their success has traditionally been assessed using a plant community approach. 18However, population ecology can also be useful to assess restoration success and to 19 understand underlying mechanisms. 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The restoration of dry grassland habitats, usually consisting of reopening the land by cutting trees and removing the litter or the topsoil, followed by mowing or grazing, aims at creating favorable conditions for seed germination and for a successful seedling development to mature individuals of the characteristic plant species (Miller & Hobbs ; Harzé et al ). The restoration of sandy grasslands can also be considered during or at the end of the exploitation of sandstone quarries, especially if populations of characteristic species remain.…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of dry grassland habitats, usually consisting of reopening the land by cutting trees and removing the litter or the topsoil, followed by mowing or grazing, aims at creating favorable conditions for seed germination and for a successful seedling development to mature individuals of the characteristic plant species (Miller & Hobbs ; Harzé et al ). The restoration of sandy grasslands can also be considered during or at the end of the exploitation of sandstone quarries, especially if populations of characteristic species remain.…”
Section: Introductionmentioning
confidence: 99%
“…The extremely low level of polymorphism in the population may have originated from somatic mutations, related to extensive vegetative propagation, but it is also compatible with relictual sexually segregating genetic diversity (Ellstrand & Roose 1987, Klekowski 1997. Somatic mutations can be a source of genetic diversity, especially when sexual reproduction is disrupted (Gross et al Van Rossum et al, Preserving endemics in highly anthropogenic landscapes 2012), as reported for the rare sterile clonal shrub Grevillea renwickiana (James & McDougall 2014) and for the clonal serpentine endemic Calystegia collina (Wolf et al 2000).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Protection of the known populations is the priority, but additional conservation efforts may be needed to recover suitable habitat conditions, especially when habitat quality has been degraded. In situ ecological management practices, often replacing traditional agro-pastoral practices, aim at restoring or maintaining habitat quality and increase population sizes of habitat specialists (Miller & Hobbs 2007, Harzé et al 2015. If restoring habitat quality of existing sites is not possible, relocation to other sites suitable for the target species may be an alternative solution (Volis 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Society for Ecological Restoration (), the ultimate goal of restoration projects is to develop an ecosystem that is self‐supporting and resilient to perturbations. Numerous criteria can be employed to evaluate the success of restoration interventions (Hobbs & Norton ; Piqueray et al ; Harzé et al ), including different disciplines (Wortley et al ) as well as various ecological complexities, that is individuals, populations, communities, ecosystems, and landscapes (Ruiz‐Jaen & Aide ; Cristofoli & Mahy ). According to Ruiz‐Jaen and Aide (), most studies use three community or ecosystem attributes to assess restoration success, that is vegetation structure, species diversity, and ecosystem processes, while population characteristics are less represented.…”
Section: Introductionmentioning
confidence: 99%